2018
DOI: 10.3389/fphar.2017.00985
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adenosine Receptors in Psychostimulant Addiction

Abstract: Adenosine receptors (AR) are a family of G-protein coupled receptors, comprised of four members, named A1, A2A, A2B, and A3 receptors, found widely distributed in almost all human body tissues and organs. To date, they are known to participate in a large variety of physiopathological responses, which include vasodilation, pain, and inflammation. In particular, in the central nervous system (CNS), adenosine acts as a neuromodulator, exerting different functions depending on the type of AR and consequent cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 205 publications
(251 reference statements)
0
44
1
Order By: Relevance
“…Adenosine activates P1 receptors (A1, A2A, A2B, and A3), which are primarily located on presynaptic terminals. Several of these receptors have been implicated in addiction [106], such as the A2AR, which is highly expressed in the striatum [107]. During withdrawal from cocaine, A2ARs are upregulated in both hippocampus and striatum of the rat [108111], although these receptors seem to differentially modulate the behavioral effects of repeated cocaine administration.…”
Section: Reciprocal Connections Between Cns Molecular Clocks and Enermentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine activates P1 receptors (A1, A2A, A2B, and A3), which are primarily located on presynaptic terminals. Several of these receptors have been implicated in addiction [106], such as the A2AR, which is highly expressed in the striatum [107]. During withdrawal from cocaine, A2ARs are upregulated in both hippocampus and striatum of the rat [108111], although these receptors seem to differentially modulate the behavioral effects of repeated cocaine administration.…”
Section: Reciprocal Connections Between Cns Molecular Clocks and Enermentioning
confidence: 99%
“…Indeed, deletion of A2ARs in striatal neurons enhanced cocaine sensitization, while deletion of the receptors in cortical and hippocampal neurons attenuated locomotor sensitization [112,113]. These receptors are involved in many other drug reward related behaviors [106]. …”
Section: Reciprocal Connections Between Cns Molecular Clocks and Enermentioning
confidence: 99%
“…All subtypes of AR are characterized by seven transmembrane domains connected by three intracellular and extracellular domains. At the extracellular level, the N-terminus presents specific glycosylation sites, while at the intracellular side, the C-terminus contains phosphorylation and palmitoylation sites, important for receptor desensitization [ 23 ]. Each AR has unique cell and tissue distribution, secondary signaling transductors, affinity for adenosine, and physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, a second study reported that either increasing or decreasing the activity at A2AR was found to prevent the aversive motivational response to withdrawal from chronic, but not acute nicotine administration [ 114 ]. It is relevant here to note that A1 receptors are widely distributed in the cortex, hippocampus, and cerebellum, while A2A receptors are localized mainly in the striatum and olfactory bulb (A2B and A3 receptors are found at low levels of expression) [ 115 ]. A2A receptors are found in receptor clusters with dopamine and glutamate receptors [ 116 ] and A2A-D2-mGlu5 receptor mosaics have been discovered [ 117 ].…”
Section: Discussionmentioning
confidence: 99%